(untitled) (Castilla. Estudios de Literatura, 2019)
Lucia Berlin has come in recent years to the panorama of cult writers, at the level of Raymond Carver or Chekhov, authors with whom he has been compared on several occasions. This work tries to analyze the stories of the two books published in Spain, Manual for women cleaning (2016) and Evening in paradise (2018) with the aim of describing the poetics and narrative strategies of the author, whose work revolves around the concept of emotional truth and has a marked intertextual and metafictional character.